APSH YI-06 EFFECTS OF ANGIOTENSIN II TYPE 2 RECEPTOR IN FETAL GROWTH RESTRICTION MICE. (September 2016) - Yamauchi, Toshifumi; Mogi, Masaki; Nakaoka, Hirotomo; Tsukuda, Kana; Kukida, Masanori; Higaki, Akinori; Bai, Hui-Yu; Shan, Bao-Shuai; Min, Li-Juan; Iwanami, Jun; Horiuchi, Masatugu
Abstract : Objective: Fetal growth restriction (FGR) is one of the risks of cardiovascular problems in adulthood. We previously reported that the vascular injury enhanced vascular remodeling in FGR mice, but the mechanisms are still unclear. Angiotensin II type 2 receptor (AT2R) is relatively highly expressed in fetal mice but not in adult mice. Therefore, we investigated the effects of AT2R in FGR mice, using AT2R knockout (AT2KO) mice. Design and method: Dams (C57BL/6J strain (WT) mice and AT2KO mice) were fed an isocaloric diet containing 20% protein (normal protein; NP) or 8% protein (low protein; LP) from 10 weeks of age until delivery. On the day of delivery, all dams were returned to the NP diet. After weaning, offspring were fed the NP diet. When offspring were 10 weeks of age, vascular injury was induced by polyethylene cuff placement around the femoral artery. At 12 weeks of age, we investigated the neointima formation in femoral artery, arterial blood pressure, body weight and histological changes of organs. Results: Birth weight in offspring from dams fed LP until delivery (LPO) was significantly lower than NPO in both WT and AT2KO mice. Body weight at 10 weeks of age and arterial blood pressure at 12 weeks of age were not significantly different among four groups. Neointima formation was exaggerated in LPO compared with NPO in WT mice, but not in AT2KO mice. Interestingly, the weight ratios of heart/body and kidney/body in AT2KO-LPO is significantly higher than these in the other groups. Conclusions: Using inflammatory vascular remodeling model, FGR promote neointima formation in WT mice, but not in mice with deletion of AT2R. In contrast, AT2KO-LPO showed a significantly higher heart/body and kidney/body weight ratios than the other groups without arterial blood pressure elevation. These results suggest that AT2R signaling may be involved in cardiovascular disorders of adult offspring with FGR.